Sticky Leverage - Gomes, João; Jermann, Urban; Schmid, Lukas (American Economic Review, 2016)
We develop a tractable general equilibrium model that captures the interplay between nominal long-term corporate debt, inflation, and real aggregates. We show that unanticipated inflation changes the real burden of debt and, more significantly, leads to a debt overhang that distorts future investment and production decisions. For these effects to be both large and very persistent, it is essential that debt maturity exceeds one period. We also show that interest rate rules can help stabilize our economy. (JEL E12, E31, E44, E52, G01, G32, G35)